Charge Transport Phenomena Unique to Diamond. Issue 1591 (13th March 2014) - Kovi, Kiran K.; Suntornwipat, Nattakarn; Majdi, Saman; Gabrysch, Markus; Hammersberg, Johan; Isberg, Jan
ABSTRACT Diamond is a unique material in many respects. One of the most well-known extreme properties of diamond is its ultrahardness. This property of diamond actually turns out to have interesting consequences for charge transport, in particular at low temperatures. In fact, the strong covalent bonds that give rise to the ultrahardness results in a lack of short wavelength lattice vibrations which has a strong impact on both electron and hole scattering. In some sense diamond behaves more like a vacuum than other semiconductor materials. In this paper we describe some interesting charge transport properties of diamond and discuss possible novel electronic applications.